(untitled) (South East Asia Journal of Public Health, 2013)
Millions of women worldwide lack the power to protect themselves from HIV; current prevention options require cooperation from the male partners. Limited prospects for an HIV vaccine and continued escalation of HIV make female-controlled HIV/STI prevention options like microbicides desirable. While socio-cultural factors could reduce acceptability of these options by vulnerable women, opinion leaders like health personnel and teachers could positively influence their acceptability. The aim of this study was to assess the acceptability of female-controlled HIV/STI prevention options among medical doctors, nurses, pharmacists and secondary school teachers in Dhaka, Bangladesh. A cross-sectional study was conducted using a self-administered semi-structured questionnaire among 375 professionals (nurses, doctors, pharmacists and teachers). The questionnaire assessed the respondents perception of HIV, and their attitudes towards female-controlled HIV/STI prevention options such as female condoms and vaginal microbicides. The study revealed that 98.4% of the respondents were of the opinion that women should determine their HIV/STI prevention options, while 89.3% agreed that options which empower women would be acceptable. It was also found that 18.4% would use the female condoms while 34.4% would use vaginal microbicides. Factors associated with willingness to use the female-controlled prevention options were HIV risk perception, marital status, profession, and duration in profession. There was no association between willingness to use female condoms and willingness to use the vaginal microbicides. While male condom use was positively associated with willingness to use female condom, there was no significant relationship between male condom use and willingness to use the vaginal microbicides. The study showed that professionals strongly supported HIV/STI prevention options that are female-controlled, with most preferring vaginal microbicides to the female condoms. Such support would inform the design of appropriate interventions to prepare the professionals for the eventual advent of an effective microbicide as a HIV/AIDS prevention option. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 46-53 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15265